SELEKSI PORTOFOLIO SEKTOR PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA (BEI) - Hendra Irwanto (Jurnal Riset Bisnis Indonesia, 2013)
The present study attempts to identify the alternative investment time in the banking sector of theindonesian capital market for the purpose of earning maximum returns. In addition, the study alsoaims to find out the alternative investment option for banking sector stocks in the capital market. Inorder to find the alternative, the four criteria were used namely the fundamental aspect of finance(asset base, gross earning, profit after tax, share capital), capital market (share price, earnings,earning per share, market capitalisation, devidends policy), management efficiency (credit policy,corporate image, structure and strategy, workforce capacity, age of bank), economic condition(interest rate, inflation). The Findings of this study suggest that the short term investment is theprefered alternative investment time and BCA/ Bank Central Asia Tbk is the preffered bank in theIndonesian stock exchange. The first important indicator for investment decision making is thefundamental aspect of finance. The sub criteria in the decisions made by investors regarding thefundamental criteria (financial criteria) is profit after tax. For the capital market, the most significataspect is earning. For management efficiency, the significat indicator is corporate image and thefor economic condition aspect, the significat indicator is inflation.Keywords: investment alternatives, capital market, Analytical Hierarchy Process (AHP)